Stochastic assembly process indicates high risks of water transfer on fish communities in waters along the East Route of the South-to-North Water Transfer Project, China - Huiguo Yan; Anxiang Wang; Fei Cheng; Zhenhao Cheng; Lei Gao; Wenping He; Songguang Xie (Global Ecology and Conservation)
Inter-basin water transfer projects can drive ecological changes such as biological invasion, community homogenization, and ecosystem instability. However, the mechanisms governing fish community responses to water transfer remain unclear. Using environmental DNA metabarcoding, we examined species composition, assemblage structure, and community assembly in three water bodies along the East Route of the South-to-North Water Transfer Project of China: Hongze Lake, Nansi Lake, and the terminal Shuangwangcheng Reservoir. 1610,564 OTUs were assigned to 53 species from 13 families and 6 orders. Cypriniformes dominated, comprising 71.7 % of species. Species richness was highest in July (48 species) compared to November (37 species) and February (38 species). Assemblage structures significantly differed among months (ANOSIM, R = 0.59, P = 0.00). Shuangwangcheng Reservoir’s assemblage was similar to the transferred communities, indicating IBWT-facilitated dispersal as a primary driver of fish community shifts. Fish diversity in Hongze Lake and Nansi Lake declined over two decades, from 84 to 73 species, with the loss of migratory and pollution-sensitive taxa. Community assembly was largely stochastic (NRI and NTI within null confidence intervals) but influenced by environmental filtering. Repeated annual transfers intensified stochastic processes, leading to homogenization. These findings highlight the ecological consequences of Inter-basin water transfer projects and underscore the need to consider long-term disturbances when designing and optimizing water transfer megaprojects.